Consumer social responsibility - Michalski, Michał A. (Annales. Etyka w Życiu Gospodarczym, 2019)
In our contemporary literature and academic discourse, we often see how popular the topic of corporate social responsibility is. It will be argued that another problem, tightly linked to this issue, and strongly influencing the business environment is the consumer behaviour. This second part of business relations is often associated rather with legal demands and customer protection. The purpose of my article is to show how consumer social responsibility can help not only the corporations but also those involved in the market exchange to contribute to the common good and improve quality of millions of transactions people make every day. To become real, this responsibility needs effort—courage to witness by expressing consumer’s opinion and education. The first aspect shows how important action is in revealing values and introducing ethics into everyday market activity, the second shows that emphasizing basic economic education and expecting thorough information from companies can help build and enhance consumer awareness. This article also attempts to demonstrate the contributions of Catholic Social Thought to the problem of social responsibility.